The specific intellectual's pivotal position: action, compassion and thinking in administrative society, an Arendtian view. (19th June 2013) - Feldman, Gregory
Abstract : Political action is frequently conceptualised as starting from the ground up. Plausible as this point may be, it pays insufficient attention to well‐established arguments that we inhabit administrative society, implicitly contrasted against political society, with technocrats operating the requisite power/knowledge grid away from the street. Like Foucault's 'specific intellectuals', technocrats work in pivotal positions in apparatuses of population regulation, but nevertheless can potentially recognise the plight of the marginalised 'masses' as they themselves are also alienated subject‐objects of population regulation. This article draws on a range of ethnographic encounters with technocrats working in diverse areas of migration management in the European Union to prompt an examination of the historical and social conditions that impede, and often render unthinkable, direct engagement between technocrats and the migrants whom they are paid to regulate. The article draws explicitly on Hannah Arendt's work on the vita activa, compassion, thinking, judging and revolution (1) to explain how the apparatus's systemic isolation of both its policy experts and policy targets impedes political action and (2) to identify a form of ethnographic engagement that might help to overcome it.